2018
DOI: 10.1016/j.gca.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

A Mesoarchean shift in uranium isotope systematics

Abstract: Oxygenic photosynthesis fundamentally transformed all major biogeochemical cycles and increased the size and complexity of Earth's biosphere. However, there is still debate about when this metabolism evolved. As oxygenic photosynthesis is the only significant source of O 2 at Earth's surface, O 2-sensitive trace element enrichments and isotopic signatures in Archean sedimentary rocks can potentially be used to determine the onset of oxygenic photosynthesis by tracking shifts in the oxidative capacity of Earth'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 110 publications
2
43
0
Order By: Relevance
“…In fact, even the scenario in which ΔT is a billion years (ν max = 5.03 ± 1.42) may be an overestimation and could potentially indicate that the age of the duplication event that led to D1 and D2 occurred immediately after the origin of the earliest reaction center. In consequence, the evolution of the core subunits of PSII is more consistent with a scenario in which oxygenic photosynthesis originated long before the GOE as supported by the geochemical record of inorganic redox proxies (Crowe et al, 2013;Havig, Hamilton, Bachan, & Kump, 2017;Planavsky et al, 2014;Wang et al, 2018).…”
Section: Sd (Ga) II D0supporting
confidence: 73%
See 3 more Smart Citations
“…In fact, even the scenario in which ΔT is a billion years (ν max = 5.03 ± 1.42) may be an overestimation and could potentially indicate that the age of the duplication event that led to D1 and D2 occurred immediately after the origin of the earliest reaction center. In consequence, the evolution of the core subunits of PSII is more consistent with a scenario in which oxygenic photosynthesis originated long before the GOE as supported by the geochemical record of inorganic redox proxies (Crowe et al, 2013;Havig, Hamilton, Bachan, & Kump, 2017;Planavsky et al, 2014;Wang et al, 2018).…”
Section: Sd (Ga) II D0supporting
confidence: 73%
“…Our present finding that the duplication leading to L and M occurred significantly later in anoxygenic Type II reaction centers opens the possibility that oxygen could have also been a driving force in their heterodimerization process, since K would have encountered these selection pressures at a time when oxygen concentrations began to rise or fluctuate in localized environments during the late Archean (Bosak, Liang, Sim, & Petroff, ; Lyons, Reinhard, & Planavsky, ; Riding, Fralick, & Liang, ; Wang et al., ). Mirroring the evolution of Type II reaction centers, a molecular clock study on Type I reaction centers showed that the duplication event that led to the heterodimerization of the core of Photosystem I was also more likely to be the oldest node after the root (Cardona et al., ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…from fossils, biomarkers or other geochemical proxies) imposed on the calculations [215][216][217][268][269][270][271][272][273]. A range of genomic and geochemical evidence nevertheless suggests that the roots of cyanobacteria and the initiation of atmospheric oxygenation pre-date the Great Oxidation Event by several hundred million years [268,271,[273][274][275][276][277][278][279][280][281]. Similarly, paleontological evidence and molecular clock estimates generally agree the roots of eukaryotic photosynthesis pre-date the Neoproterozoic Oxidation Event by at least several hundred million years [215][216][217]269,272].…”
Section: Fe 3+mentioning
confidence: 99%